2009
DOI: 10.1111/j.1365-2427.2008.01993.x
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity of Belgian groundwater fauna in relation to environmental conditions

Abstract: SUMMARY1. The Pleistocene glaciations during the Quaternary appear to have resulted in an impoverished groundwater fauna in northern Europe. Re-colonisation may have occurred either through long-distance dispersal from unglaciated southern areas or from local refugia. 2. The Belgian groundwater fauna was sampled at multiple sites, and its habitats characterised, to assess whether the composition of present-day stygobiotic assemblages can be attributed to either of these mechanisms. 3. A total of 202 sampling s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
56
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(67 citation statements)
references
References 27 publications
9
56
2
Order By: Relevance
“…Given that individual boreholes are just point samples in a potentially extensive habitat, and that previous studies (in other geologies) have suggested that multiple sampling occasions are often required to detect species in boreholes (Allford et al 2008;Eberhard et al 2009;Hancock and Boulton 2009), it is remarkable that 67 % of our borehole samples detected stygobitic invertebrates on just a single sampling occasion. It is clear that the Chalk represents an important and widespread habitat for groundwater adapted invertebrates in England, and is likely to do so throughout Europe, where similar hydrogeological conditions exist (Downing et al 2005), and fauna have been previously recorded Martin et al 2009;Michel et al 2009). …”
Section: The Importance Of the Chalk As An Ecological Habitatmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that individual boreholes are just point samples in a potentially extensive habitat, and that previous studies (in other geologies) have suggested that multiple sampling occasions are often required to detect species in boreholes (Allford et al 2008;Eberhard et al 2009;Hancock and Boulton 2009), it is remarkable that 67 % of our borehole samples detected stygobitic invertebrates on just a single sampling occasion. It is clear that the Chalk represents an important and widespread habitat for groundwater adapted invertebrates in England, and is likely to do so throughout Europe, where similar hydrogeological conditions exist (Downing et al 2005), and fauna have been previously recorded Martin et al 2009;Michel et al 2009). …”
Section: The Importance Of the Chalk As An Ecological Habitatmentioning
confidence: 99%
“…However, in general, groundwater ecosystems are not considered in water management programs. Nevertheless the Chalk aquifer has been identified as a habitat for invertebrate groundwater fauna in England (Proudlove et al 2003;Robertson et al 2009;Sorensen et al 2013;Johns et al 2015), and fauna are recorded from Chalk areas in continental Europe Martin et al 2009;Michel et al 2009); however, it is unclear in some of these studies which samples came from the Chalk, and questions remain about where in the aquifer invertebrates occur, and how commonly they occur. The prevalence of species in the Chalk and the importance of the Chalk as an ecological habitat have not been properly assessed.…”
Section: Introductionmentioning
confidence: 99%
“…Gibert & Deharveng, 2002;Castellarini et al, 2005;Galassi et al, 2009b;Martin et al, 2009) give rise to groundwater biodiversity patterns, how they interact is far from being known. Until now, spatial patterns of groundwater biodiversity have been basically interpreted under an ecological perspective.…”
Section: Introductionmentioning
confidence: 99%
“…The few taxa found with higher abundances such as Acanthocylops robustus, A. sensitivus Diacyclops languidoides (table 5 -supplementary data) but also the more rarely found isopod [Proasellus coxalis Proasselus cavaticus) and amphipod [Crangonyx subterraneus] taxa are basically widespread and commonly found throughout Austria but also Europe (e.g. Gaviria 1998;Danielopol and Pospisil, 2001;Fuchs et al, 2006;Kaiser, 2005;Hahn and Fuchs, 2009;Martin et al, 2009). Comprehensive aquifer studies including other nematode data than their total numbers or relative portions are to our present knowledge not existent, but abundances of total nematode fauna can be relatively high in both alluvial and fissured aquifer types compared to other faunal elements (Fuchs et al, 2006).…”
Section: Resultsmentioning
confidence: 99%